Analisis Ketersediaan Air Pompanisasi Air Irigasi Daerah Irigasi Rawa Sepotong Kabupaten Bengkalis Dengan Metode F.J Mock - Harry Dias Darmawan; Siswanto Siswanto; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Bengkalis Regency has rice fields with an area of 5,014 ha. The extent of this rice field is a potential that can support the availability of food to meet local and regional needs. One of the irrigation areas in Bengkalis Regency is the Daerah Irigasi Rawa Sepotong in Langkat Village. This irrigation has an area of 326 ha and is a rainfed irrigation area that only utilizes rainfall to meet irrigation water needs. Although in the rainy season the irrigation water needs are met, in the dry season the rainfall is not able to meet the irrigation water needs. One alternative source of water for this irrigation area can be taken from the Siak Kecil River. However, the water level of the Siak Kecil River is lower than the elevation of the rice fields, so pumping is needed to drain the water. This research was conducted by using various secondary data and analyzing the feasibility of the pumping development. Based on the data analysis, it was found that the availability of reliable discharge (Q80) of the Siak Kecil River using the F.J Mock method was 31.5 m3/s with the highest irrigation water requirement in August period I of 0.68 m3/s. With a very high level of water availability compared to the irrigation water needs of the area, technically the construction of irrigation pumping is feasible. Keywords: F.J Mock method, feasibility, irrigation, irrigation water needs, pumping, water availability.